Zinc and amino acids impact on nutrient status of maize during the 'critical window' - Witold SZCZEPANIAK; Jarosław POTARZYCKI; Witold GRZEBISZ; Bartłomiej NOWICKI (Plant, Soil and Environment, 2018)
It has been assumed that zinc (Zn) fertilizers applied to maize simultaneously with amino acids (AA) at early stages of its growth may decrease the yield variability due to correcting its nutritional status during the 'critical window'. Two Zn carriers were evaluated (Zn-I - Zn chelate; Zn-II - Zn oxide); they were applied to maize at BBCH 14/15 with or without amino acids, based on two rates of nitrogen (80 and 160 kg N/ha). The precipitation deficiency in 2015 resulted in the grain yield decrease by 35% compared to 2014. An advantage of higher N rate was proved in 2014, whereas the influence of Zn and AA showed in 2015. In this year, the beneficial impact of Zn-oxide and AA combined application resulted in amelioration, at least partially, of the imbalance of certain macronutrient content (N, P, Mg) during the 'critical window'. These effects were revealed due to a boosted number of kernels in cob, and particularly higher thousand kernel weight. Consequently, the yield depression in 2015 was partly overcome. The results indicated that simultaneous application of Zn oxide and AA to maize at BBCH 14/15 corrected both its nutritional status during the 'critical window' and yield components, but had no effect on the yield itself.